2022
DOI: 10.1016/j.isci.2021.103687
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment-gut interactions in Huntington's disease mice are associated with environmental modulation of the gut microbiome

Abstract: Summary Gut dysbiosis in Huntington's disease (HD) has recently been reported using microbiome profiling in R6/1 HD mice and replicated in clinical HD. In HD mice, environmental enrichment (EE) and exercise (EX) were shown to have therapeutic impacts on the brain and associated symptoms. We hypothesize that these housing interventions modulate the gut microbiome, configuring one of the mechanisms that mediate their therapeutic effects observed in HD. We exposed R6/1 mice to a protocol of either EE o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…1C ), consistent with our recent findings. 12 However, an increase in gut permeability at the late disease stage (Week 20) was detected in both male and female Huntington’s disease mice compared with WT littermate controls ( P = 0.02 and P = 0.03, respectively) ( Fig. 4C ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…1C ), consistent with our recent findings. 12 However, an increase in gut permeability at the late disease stage (Week 20) was detected in both male and female Huntington’s disease mice compared with WT littermate controls ( P = 0.02 and P = 0.03, respectively) ( Fig. 4C ).…”
Section: Resultsmentioning
confidence: 91%
“… 5–8 R6/1 transgenic Huntington’s disease mice express the mutant human HTT transgene and provide an excellent preclinical model, exhibiting progressive cognitive, behavioural, cellular and molecular deficits closely modelling clinical Huntington’s disease, 9–11 including the onset of gut dysfunction at early stages of the disease with the potential to worsen with disease progression. 12 …”
Section: Introductionmentioning
confidence: 99%
“…In the context of HD, a preclinical model of HD exercise was able to delay the onset of the disease and cognitive impairment [ 202 ]. Recently, a study revealed the main bacterial signature (the orders of Bacteroidales, Lachnospirales, and Oscillospirales) that discriminates the effect of exercise and environmental enrichment in wild-type and HD mice, suggesting a promising role for the gut microbiome in mediating the positive effects of these interventions in HD [ 203 ].…”
Section: Exercise and Gut Microbiotamentioning
confidence: 99%
“…This protocol can help to improve reproducibility of results from studies involving environmental enrichment and exercise by offering consistent housing conditions between laboratories. For complete details on the use and execution of this protocol, please refer to Gubert et al. (2021) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Gubert et al. (2021) .…”
mentioning
confidence: 99%